Mesh independence study on CFD for Cryo-CO2 cooling strategy - Nur Fatini, Mohamad Fauzee; Nurul Hayati, Abdul Halim; Zainoor Hailmee, Solihin; Izdihar, Tharazi; Nor Hayati, Saad; Zulaika Zulkifli, Saad; Musfirah, Abdul Hadi (UiTM Press, 2024)
This study conducts comprehensive mesh independence tests to identify the optimum mesh independence parameters that offer the most feasible Computational Fluid Dynamic (CFD) analysis on cryo-CO2 temperature variations and its heat transfer performance under cryo-CO2 cooling strategy in metal cutting. ANSYS Fluent was used to conduct the CFD study with its mesh control parameters (relevance center and smoothing) designed using Response Surface Methodology (RSM) under Central Composite Design (CCD). An Analysis of Variance (ANOVA) was applied to analyse how the controlled factors influenced the cryo-CO2 flow temperature when it flowed from the nozzle to the tooltip. The analysis found that the relevance centre was more significant in influencing the accuracy of the response value. For optimization, the combination of medium relevance center and smoothing meshes was suggested to develop the lowest cryo-CO2 flow temperature at 256.85 K. This is crucial since most machining outputs are heat dependent. Experimental data sets were used to validate the predicted result. Distances between 3.6 to 18 mm showed an acceptable deviation of ~0.4 – 0.6% and ~0.4 – 4.2% for simulated and experimented work, respectively. This value is acceptable, and the generated quadratic model equation can be applied for prediction. The heat transfer performance of the cryo-CO2 flow at tool-chip and tool-workpiece interfaces under high-speed machining was also discussed. Moreover, further analysis using the optimal solution has led to a better understanding of heat transfer in cryogenic carbon dioxide (CO2), resulting in enhanced cooling of the cutting zone and improved machining processes.